2013
DOI: 10.1021/nn403625s
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Analysis of DNA Conformation Changes Induced by Transcription Factor Complex Binding Using Plasmonic Nanodimers

Abstract: The plasmon resonant wavelength for a pair of gold nanoparticles, or gold nanodimer, increases inversely with the gap distance between the two nanoparticles. Taking advantage of this property, we performed nanoscale measurements of DNA conformation changes induced by transcription factor binding. Gold nanoparticles were bridged by double-stranded DC5 DNA that included binding sequences for the transcription factors SOX2 and PAX6, which interact on the DC5 enhancer sequence and activate transcription. The gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…A recent study on Sox2 and Pax6 cooperativity used plasmon resonance and gold nanoparticles tethered to the end of DC5 and DC5con sequences. While Sox2 alone induced indistinguishable bends, it was reported that the DC5 is more markedly deformed by Sox2–Pax6 dimers than the DC5con element ( 65 ). Apparently, Sox2–Pax6 binding induces structural changes to DNA in a sequence-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on Sox2 and Pax6 cooperativity used plasmon resonance and gold nanoparticles tethered to the end of DC5 and DC5con sequences. While Sox2 alone induced indistinguishable bends, it was reported that the DC5 is more markedly deformed by Sox2–Pax6 dimers than the DC5con element ( 65 ). Apparently, Sox2–Pax6 binding induces structural changes to DNA in a sequence-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The programmed assembly of gold nanoparticles (AuNPs) on DNA scaffolds is a powerful technique to design metamaterials for applications such as plasmon‐enhanced spectroscopy, chemical sensing, and molecular rulers, as well as for the development of novel imaging and therapeutic agents . All of these examples rely on the collective optical response of AuNP groupings and therefore on distance‐dependent plasmon coupling.…”
Section: Introductionmentioning
confidence: 99%
“…We used DNA strands with 23 bases. Given the lengths of particlethiol and DNA-fluorophore linkers (%1.8 nm) [18][19][20], the distance between the fluorophore and metal particles is about 9.6 nm, which is longer than the Forster distance, 9 nm, calculated by Yun for case of energy transfer from an organic fluorophore to a gold nanoparticle [17]. Therefore, the energy transfer efficiency is below 50%, and sufficient fluorescence intensity can be obtained for performing measurements.…”
Section: Structure Of the Fluorescent Probementioning
confidence: 95%